Achieving sustainability by additive manufacturing: a state-of-the-art review and perspectives - Jinlong Su; Wei Long Ng; Jia An; Wai Yee Yeong; Chee Kai Chua; Swee Leong Sing (Virtual and Physical Prototyping)
As global awareness of resource scarcity and environmental concerns grows, sustainable manufacturing practices have become imperative. Additive manufacturing (AM), with its high material efficiency and design flexibility, presents a promising pathway toward sustainable industrial transformation. This review explores AM's role in sustainability across its lifecycle: design for AM, in AM, and after AM. In the design for AM phase, strategies such as topology optimisation, part consolidation, and cellular structures reduce material usage and enhance durability. During AM, in-situ process monitoring and closed-loop control improve process reliability, reducing energy consumption and failure rates. Meanwhile, the adoption of sustainable materials—metals, polymers, concretes, and biomaterials—further strengthens AM's potential to advance sustainability. After AM, applications such as repair, remanufacturing, and recycling extend product lifecycles and reduce environmental impact, aligning with circular economy principles. Future perspectives include the integration of artificial intelligence for in-process control and sustainable material development, along with regulatory and circular economy frameworks critical to sustainable AM deployment. Lastly, emerging research trends in advancing sustainability through AM are reviewed. Overall, this review provides a roadmap for academia and industry, offering strategies and insights to maximise AM's contribution to a more sustainable and responsible manufacturing future.